Time Trends of Epidemiology of Hemorrhagic Stroke among Urban Population in Kazakhstan - Zhukov, Yevgeniy; Dyussembekov, Yermek Kavtaevich Kavtaevich; Aringazina, Аltyn; Kastey , Rauan; Nikatov, Kuanysh; Tamasauskas, Arimantas; Kulmanbetov, Ruslan; Tursynbekova, Anar; Almabayev, Ydyrys (Open Access Macedonian Journal of Medical Sciences, 2022)
AIM: Central Asia has been known among the highest hemorrhagic stroke (HS) and subarachnoid hemorrhage (SAH) burden regions globally. Despite the decline in cardiovascular disease mortality (CVD), HS and SAH have been remaining a public health concern in Kazakhstan. This study aimed to evaluate the trends of HS and SAH among the urban population in Kazakhstan. METHODS: We studied HS and SAH cases aged 18 years and older between 2013 and 2017 hospitalized to stroke centers in Almaty (Kazakhstan). HS and SAH were confirmed by neuroimaging. We calculated age-standardized event, mortality and in-hospital case-fatality rates (per 100,000 populations) with 95% CIs for each individual year and over the five years using SAS University Edition and Joinpoint Regression Program. RESULTS: Out of 2759 HS and 413 SAH cases admitted into the stroke centers of Almaty (Kazakhstan), 27.4% cases died in a hospital. The age-standardized HS event rates decreased in both sexes over the five years while age-standardized SAH event rates increased for the same period of time. The age-standardized mortality and case-fatality rates decreased in women among HS and SAH cases and men with HS. However, the age-standardized mortality and case-fatality SAH rates increased in men over same period. CONCLUSIONS: Despite the overall decline in HS and slight increase in SAH over the 5 years, the burden remains high. We need to further monitor HS and SAH trends to develop targeted interventions and ensure that the preventive strategies are reducing the burden.